Using Online Media To Study Animal Cognition: Domestic Cat Responses To Reflective Images - Kim Youngbean; Philip Johns (Animal Behavior and Cognition)
In the mirror test of visual self-recognition, if an animal responds to its reflection as its own, rather than how it would respond to a novel individual, the animal may have the capacity to recognize itself in mirrors. Previous studies have offered little information about self-recognition of domestic cats. Here we explore two phenomena that may shed light on whether cats recognize their own reflections or reflective images by gleaning data from social media. We examine TikTok videos where pet owners show cats reflective images with augmented reality (AR) filters; and YouTube videos where cats interact with mirrors. Behavioral sequence analysis revealed little support that cats understand reflective images. Few TikTok cats responded to augmented reality images, and their responses may have been triggered by other cues, such as human touch. In YouTube videos, cats fell into five behavioral clusters, two which were aggressive, and two which were curious. Even curious cats showed little evidence that they have the prerequisite conditions to be tested for mirror self-recognition. We consider whether distinct clusters may indicate that cat personality influences how cats respond to their reflections. We discuss the utility of social media for addressing questions of animal cognition.